Under Sleeper Pads in Switches & Crossings - Plášek, Otto; Hruzíková, Miroslava (IOP PUBLISHING LTD, DIRAC HOUSE, TEMPLE BACK, BRISTOL BS1 6BE, ENGLAND, 2017)
Under sleeper pads (USPs) have been installed in the Czech railway lines since 2007 into two trial sections in switches and crossings and in a trial section with the aim to reduce rail pitch corrugation. The basic motivation for the construction of the trial track sections in turnouts was an evaluation of USPs' influence on improvement of track quality as a consequence of ballast bed protection against extreme stress. The paper comprises experience of USPs installation in the Czech Republic in the two trial sections with switches and crossings built in 2007 and 2014. The paper particularly provides an information about USPs applications focusing on the track settlement received by an evaluation of data from the geodetic surveying by precise levelling. Some positive influence of under sleeper pads on the track quality is observed.

Under sleeper pads (USPs) have been installed in the Czech railway lines since 2007 into two trial sections in switches and crossings and in a trial section with the aim to reduce rail pitch corrugation. The basic motivation for the construction of the trial track sections in turnouts was an evaluation of USPs' influence on improvement of track quality as a consequence of ballast bed protection against extreme stress. The paper comprises experience of USPs installation in the Czech Republic in the two trial sections with switches and crossings built in 2007 and 2014. The paper particularly provides an information about USPs applications focusing on the track settlement received by an evaluation of data from the geodetic surveying by precise levelling. Some positive influence of under sleeper pads on the track quality is observed.
Under Sleeper Pads in Switches & Crossings
Keywords: railway infrastructure; switches and crossings; under sleeper pads; railway infrastructure; switches and crossings; under sleeper pads